Hubungan Iklan Red Bull sebagai Citra Merek Sponsor Olahraga Ekstrem - Herny Arya Ardiansyah; Arfian Suryasuciramdhan; Ivan Aditia Putra; Imam Budiansyah; Bagus Maulana Ramadhan (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
This study analyzes Red Bull advertisements as a form of visual propaganda that effectively constructs a brand image associated with extreme sports, bravery, and extraordinary achievement. The background of this research lies in the phenomenon of the increasing prevalence of visual content in modern marketing strategies, which not only sell products but also embed ideologies and social identities. Red Bull was selected as the object of study due to its consistent use of visual elements rich in symbolic and connotative meaning. This research employs a qualitative approach using Roland Barthes' semiotic analysis method, along with theories of visual propaganda and social identity. The findings reveal that Red Bull communicates its message not merely through images and slogans, but also through the construction of deep connotative meanings. The slogan “Red Bull Gives You Wings” instills a sense of hope in surpassing one's limits, while the use of extreme sports figures as testimonials reinforces the product's image as a symbol of high performance. These advertisements create a modern myth in which Red Bull is associated with courage and freedom, transforming it from a mere energy drink into a lifestyle identity. In the context of social identity, consumers are not only purchasing a product but also affirming themselves as members of an adventurous, active, and daring community. Thus, Red Bull successfully builds brand loyalty through a strong and symbolic visual narrative. This research emphasizes that today’s advertisements are inseparable from ideological functions and the social constructions they visually shape.